Powerful laser pulse absorption in partly homogenized foam plasma. (30th March 2016) - Cipriani, M.; Gus'kov, S.Yu.; Angelis, R. De; Andreoli, P.; Consoli, F.; Cristofari, G.; Giorgio, G. Di; Ingenito, F.; Rupasov, A.A.
Abstract: The internal volume structure of a porous medium of light elements determines unique features of the absorption mechanism of laser radiation; the characteristics of relaxation and transport processes in the produced plasma are affected as well. Porous materials with an average density larger than the critical density have a central role in enhancing the pressure produced during the ablation by the laser pulse; this pressure can exceed the one produced by target direct irradiation. The problem of the absorption of powerful laser radiation in a porous material is examined both analytically and numerically. The behavior of the medium during the process of pore filling in the heated region is described by a model of viscous homogenization. An expression describing the time and space dependence of the absorption coefficient of laser radiation is therefore obtained from the model. A numerical investigation of the absorption of a nanosecond laser pulse is performed within the present model. In the context of numerical calculations, porous media with an average density larger than the critical density of the laser-produced plasma are considered. Preliminary results about the inclusion of the developed absorption model into an hydrodynamic code are presented.